2012
DOI: 10.1007/s12072-012-9414-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA as a potential marker to predict carbon tetrachloride-induced acute liver injury in rats

Abstract: CFD may be a useful biomarker for the prediction and measurement of ALI. There is no evidence to suggest that CFD is superior to other available noninvasive biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In a separate investigation, cfDNA levels were assessed in an animal model with induced liver injury, revealing elevated cfDNA levels alongside other specific biomarkers. Nonetheless, this study acknowledges that cfDNA elevation post-tissue damage may limit its clinical utility and impact on prognostic evaluations [77].…”
Section: Cell-free Dnamentioning
confidence: 94%
See 1 more Smart Citation
“…In a separate investigation, cfDNA levels were assessed in an animal model with induced liver injury, revealing elevated cfDNA levels alongside other specific biomarkers. Nonetheless, this study acknowledges that cfDNA elevation post-tissue damage may limit its clinical utility and impact on prognostic evaluations [77].…”
Section: Cell-free Dnamentioning
confidence: 94%
“…Extracellular DNA, or cfDNA, is the DNA molecule released, whole or fragmented, into body fluids of healthy subjects, such as blood, saliva, urine and/or feces [64,65], from a nucleated cell, and its level is usually much higher in people after physical effort [65]; however, in patients with various diseases such as sepsis, the inflammatory stress significantly increases many markers as well as the cell-free DNA level [56,[63][64][65][66][67][68][69]. Additionally, cf-DNA has been suggested as a potential predictive biomarker for several different conditions, including cancer (currently allows determination of a small fraction of tumor-derived) [70][71][72], stroke [73], trauma [74], transplantation (early detection of allograft rejection) [68,69,75,76], AKI [77,78], inflammatory and autoimmune diseases [79], and pregnancy (huge impact on prenatal medicine, where non-invasive prenatal testing is based on analysis of a fetal component of cfDNA in maternal blood) [80].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…Interestingly, the characterization of cfDNA derived from the microbiome of non-human primates may allow the discovery and monitoring of taxa that cause zoonotic diseases [ 108 , 486 ]. Furthermore, various animal models have been used to study correlations between different pathological factors and corresponding changes in cfDNA, which may have implications in human biology and pathology, such as the study of traumatic brain injury in rats [ 487 ], carbon tetrachloride-induced acute liver injury in rats [ 488 ], perinatal asphyxia in piglets [ 489 ], tumor progression and metastases in rats [ 490 , 491 ], the onset of parturition in mice [ 492 ], and gateways regulating the release of tumor-derived cfDNA in mice [ 493 ].…”
Section: Characterization Of Cfdna In Animalsmentioning
confidence: 99%
“…Those ecDNA molecules which circulate in the blood have been proposed as markers of various diseases. For instance, it has been suggested as a possible marker of hepatic fibrosis [ 124 ], nonalcoholic fatty acid liver disease [ 125 ] or as a valuable tool to predict carbon tetrachloride-induced liver injury in rats [ 126 ] and even progression toward hepatocellular carcinoma [ 127 ]. Contradictory evidence was provided by Blasi et al [ 128 ], who found higher levels of ecDNA in patients with acute-on-chronic liver failure compared to acute decompensation cirrhosis, although the amount of MPO-DNA complexes as the marker of NETs in the acute-on-chronic liver failure patients was not elevated.…”
Section: Citrullination Nets and Pads In Chronic Diseasesmentioning
confidence: 99%